2014
DOI: 10.9790/0661-16178191
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive and multivariable analysis of the water parameters quality of Sfax sewage treatment plant after rehabilitation

Abstract: This study detailed the effect of simultaneous multiple intrinsic and extrinsic factors on the characteristics of Sfax activated sludge wastewater treatment plant (WWTP), located in Southern East Tunisia. The plant performance was evaluated through descriptive and statistical analysis of quantity and quality data of both raw wastewaters and treated effluent over a period of three years (2008-2010). Despite the rehabilitation, poor performance was shown to be attributed to raw wastewaters quality, civilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…It was seen in this work that measured pH values were consistently increased by between 0.3 and 0.9 units giving relatively stable daily, weekly and monthly average pH effluent Journal of Water Resource and Protection between 7.94 and 8.14 ( Table 2). This observation is consistent with the works of Belhaj and coworkers [7].…”
Section: Qualitative Analysis Of Process Influent and Effluentsupporting
confidence: 94%
See 2 more Smart Citations
“…It was seen in this work that measured pH values were consistently increased by between 0.3 and 0.9 units giving relatively stable daily, weekly and monthly average pH effluent Journal of Water Resource and Protection between 7.94 and 8.14 ( Table 2). This observation is consistent with the works of Belhaj and coworkers [7].…”
Section: Qualitative Analysis Of Process Influent and Effluentsupporting
confidence: 94%
“…The Mudor waste water treatment plant uses the Up-flow Anaerobic Sludge Blanket (UASB) reactor as a unit for sewage treatment ( Figure 1) and research has indicated that about 65% to 80% of organic matter removal efficiency can be obtained in conventional UASB reactors even with short retention time of about 4 to 6 hours in hot climate areas [2]. The process of the rehabilitation of the to environmental and public health [7]. Research has also indicated that in developing countries 1.8 million people, mostly children, die every year as a result of water-related diseases [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of faecal organisms as indicator of water quality has been widely used by many researchers. According to Belhaj et al [33], public health protection concepts originated from such studies. High load could be attributed to unfavorable internal conditions which inhibit the treatment process.…”
Section: Microbial Loadmentioning
confidence: 99%
“…The decomposition of organic fractions of wastewater, mainly by microbes in water, produces some acidic species of mineralized organic materials (CO2, ammonia, NO3 -and organic acids) which plays an important role in shifting of pH scale of treated water 11 .…”
Section: In-situ Field Conditionsmentioning
confidence: 99%